Random walk in Malaysian initial public offering - Mohd Rashid, Rasidah; Narayansamay, Cheedradevi; Hashemoghli, Athena (Malaysia Finance Association, 2011)
Efficient market phenomenon states that price of stocks should fully reflect all available information in the market. This study examines weak form efficient market hypothesis in initial public offering (IPOs) in the context of recent global financial crisis. This research tests the efficiency of IPO prices based on daily return and examines the random walk hypothesis in IPOs. For the purpose of testing this study employs runs test, Jarque-Bera test, Augmented Dickey Fuller (ADF), and Philips Perron (PP). The tests concluded that daily prices are not normally distributed and IPOs do not follow random walks for the year 2006 to 2010. Therefore, investors can make arbitrage opportunities across these IPOs.